PENGEMBANGAN STRATEGI LITERASI DASAR UNTUK MENINGKATKAN MINAT BACA SISWA KELAS 2 DI SDN 106835 LIMAU MANIS - Alfitriana Purba; Aliya Ramadani; Aznisya Ajeng Putri; Refy Ristika; Indry Ayu Lizahra; Dira Salsabila Bilbina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop basic literacy strategies to enhance reading interest among 2nd-grade students at SDN 106835 Limau Manis. Using a qualitative descriptive approach, the findings show that students have a high interest in storybooks and strong confidence in classroom reading. However, internal motivation for daily independent reading remains low as it is not yet a primary leisure activity. Consequently, structured strategies through habituation, development, and learning phases are essential to establish a consistent school literacy culture